Kajian Tumbuh Kembang Balita Usia 12-59 Bulan Berdasarkan Perspektif Pendapatan Keluarga dan Riwayat Pemberian Asi Ekslusif - Gusti Lestari Handayani; Abbasiah Abbasiah; Hestiani Rohmah (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the growth and development of toddlers aged 12-59 months based on family income and history of exclusive breastfeeding. This research method is an analytic observational study with a cross-sectional design. The results showed that 50.5% had a family income above the minimum wage. History of exclusive breastfeeding, 46.4% received an account of exclusive breastfeeding. Variable growth, as many as 71.1% have normal nutrition, and 28.9% have less food. The developmental variable was obtained as 69.1% had appropriate development, and 30.9% had dubious action. The chi-square test showed a relationship between growth and development with family income (p-value = 0.000) and a history of exclusive breastfeeding (0.000). In conclusion, growth and development are strongly influenced by family income and a history of exclusive breastfeeding, where there is a tendency for mothers who have high incomes and give exclusive breastfeeding will tend to have good growth and development of toddlers. Keywords: Exclusive Breastfeeding, Toddlers, Income Growth